(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
A method has been developed for the production of a radiovaccine against piroplasmosis in cattle. When studying the reactogenic properties, a weak virulence of the vaccine material irradiated at a dose of 35 krad was revealed, and the preservation of immunogenicity up to 6 months after immunization was noted